Production of High Alpha Cellulose Pulp from Albizia amara, Acacia planifrons and Mixture of Hardwoods - Guha, S. R. D.; Singh, Man Mohan; Bhola, P. P. (Indian Forester, 1976)
High alpha cellulose pulps have been prepared from Albizia amara and Acacia planifrons and mixture of hardwoods compressing of Artocarpus sp., Dyera sp.,(Jilutong), Shorea sp. (red meranti) and Shorea sp. or Parashorea (meranti) by water-prehydrolysis sulphate process followed by multistage bleaching. These pulps could be considered for preparing various products like viscose rayon, tyre cord, nitrocellulose etc., provided these pulps pass further tests required.